Development of a multiplex bead-based assay for detection of Hepatitis C virus - Fonseca, Bruna P. F. (2011)
Fundação Oswaldo Cruz. Instituto de Tecnologia em Imunobiológicos. Laboratório de Tecnologia Diagnóstica. Rio de Janeiro, RJ, Brasil.